1992 BUDGET PUBLIC AFFAIRS DIVISION COST CENTER EXCISE ISSUE NO. 1305 (Tufts Archival Research Center, 2007)
Confidential; Budget for 1992 for the Tobacco Institute (TI) on the excise tax issue. Totals approximately $2 million, and includes funding for the "Tax Burden on Tobacco" program, consultants, and administrative fees. Funds the TI Labor Management Committee (LMC), giving support to citizens groups, particularly tax reform groups.